Foreign debt, capital controls, and secondary markets: Theory and evidence from Nazi Germany - Andrea Papadia; Claudio A. Schioppa (Humboldt University Berlin, 2020)
We show how elite capture affects optimal debt repatriations and management of official reserves under capital controls, bridging literature on debt buybacks and secondary markets. The model we provide guides our study of one of history's largest debt repatriations -in 1930s Germany. Authorities kept private repatriations under strict control -avoiding detrimental macroeconomic effects- while allowing discretionary repatriations so to reap internal political benefits. German assets exhibited large spreads between their domestic and foreign prices, granting arbitrage profits to those who had forex access. New data reveals that spread dynamics were affected by the impact of capital controls on secondary markets.
urn:nbn:de:kobv:11-110-18452/22748-0
Keywords: E65; F38; H63; N24; 330; Sovereign risk; Capital controls; Elite capture; Germany; Nazi regime; Foreign debt; Secondary markets